2020
DOI: 10.1126/science.aay3983
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific open chromatin in human iPSC neurons elucidates functional disease variants

Abstract: Most neuropsychiatric disease risk variants are in noncoding sequences and lack functional interpretation. Because regulatory sequences often reside in open chromatin, we reasoned that neuropsychiatric disease risk variants may affect chromatin accessibility during neurodevelopment. Using human induced pluripotent stem cell (iPSC)–derived neurons that model developing brains, we identified thousands of genetic variants exhibiting allele-specific open chromatin (ASoC). These neuronal ASoCs were partially driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(143 citation statements)
references
References 84 publications
5
134
0
Order By: Relevance
“…Second, we applied dCas9 to retarget the SZ risk SNP rs7148456 associated with allele-specific open chromatin at the BAG5 locus [61]. In 2 hiPSC lines, we transfected a customized ABEmax vector system [72] to express gRNA, dCas9, and ABEmax in a single vector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we applied dCas9 to retarget the SZ risk SNP rs7148456 associated with allele-specific open chromatin at the BAG5 locus [61]. In 2 hiPSC lines, we transfected a customized ABEmax vector system [72] to express gRNA, dCas9, and ABEmax in a single vector.…”
Section: Resultsmentioning
confidence: 99%
“…For testing bulk DNA base editing efficiency, we used a customized pβactin-ABEmax-puro vector system for which we cloned the dCas9-adenine base editor part from the ABEmax vector (Addgene, #112095) [59] into the pSpCas9(BB)-2A-Puro (PX459) V2.0 vector (Addgene, #62988) [60]. We edited a common SNP rs7148456 that showed allele-specific open chromatin in BAG5 [61] in 2 hiPSC lines: CW70372 (low PRS) and CW30525 (high PRS). Cells for editing were plated on 4-well dishes (Thermo Scientific) coated with Matrigel (Corning).…”
Section: Methodsmentioning
confidence: 99%
“…In our work, we overcome these limitations by taking advantage of a large collection of ASC variants in iPSC-derived neuronal cells. Unlike eQTLs, ASC variants are inside or very close to open chromatin regions, and most of them are expected to be functional [90]. Using this dataset, we demonstrated that our MetaChrom predicted variants are much more likely to be ASC variants than methods that do not take into account specific biological contexts (Figure 4).…”
Section: Discussionmentioning
confidence: 91%
“…One limitation is that we do not yet have a single quantitative metric that combines statistical associations with deep learning based functional predictions. In our recent study [90], we show that it is possible to use ASC variants as functional information as prior in Bayesian fine-mapping. It would be interesting to extend such strategy to MetaChrom predictions.…”
Section: Discussionmentioning
confidence: 93%
“…To systematically identify the SLE genetic risk variants that contribute to transcriptional dysregulation in the EBV-transformed B cell line GM12878, we designed and applied a massively parallel reporter assay (MPRA) [18][19][20][21][22][23][24][25][26][27] (Figure 1, Supplemental Figure 1). MPRA extends standard reporter assays, replacing low-throughput luciferase with high-throughput mRNA expression detection.…”
Section: Introductionmentioning
confidence: 99%